Cytotoxic and natural killer cell stimulatory constituents of Phyllanthus songboiensis - Ren, Yulin (Phytochemistry, 2015)
A dichapetalin-type triterpenoid and a dibenzylbutyrolactone-type lignan, together with five known lignans, a known aromatic diterpenoid, and a known acylated phytosterol, were isolated from the aerial parts of Phyllanthus songboiensis, collected in Vietnam. Their structures were determined by interpretation of the spectroscopic data, and the inhibitory activity toward the HT-29 human colon cancer cells of all isolates was evaluated by a cytotoxicity assay. The known arylnaphthalene lignan, (+)-acutissimalignan A, was highly cytotoxic toward HT-29 cells, with an IC(50) value of 19 nM, but this compound was inactive as a DNA topoisomerase IIα (topo IIα) poison. The known phytosterol, (−)-β-sitosterol-3-O-β-D-(6-O-palmitoyl)glucopyranoside, was found to stimulate natural killer (NK) cells at a concentration of 10 μM in the presence of interleukin 12 (IL-12).